Effect of 8 days of water-only fasting and vigorous exercise on anthropometric parameters, lipid profile and HOMA-IR in middle-aged men - Pilis Karol; Pilis Anna; Stec Krzysztof; Antosiewicz Jędrzej; Ślęzak Andrzej; Zalejska-Fiolka Jolanta; Dolibog Paweł; Pilis Wiesław; Letkiewicz Sławomir (Sciendo, 2023)
Study aim: The aim of the present study was to determine the effect of 8 days of water-only fasting and physical exercise on somatic variables, lipid profile, insulin resistance and cardiovascular function in middle-aged men.